2022
DOI: 10.23876/j.krcp.21.250
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure trajectories and blood pressure variability in kidney transplant recipients: a comparative study against chronic kidney disease patients

Abstract: Background: Hypertension is a major cardiovascular risk factor in both kidney transplant recipients (KTRs) and patients with chronic kidney disease (CKD). Ambulatory blood pressure monitoring (ABPM) is considered the gold-standard method for hypertension management in these subjects. This is the first study evaluating the full ambulatory blood pressure (BP) profile and short-term BP variability (BPV) in KTRs versus CKD patients without kidney replacement therapy. Methods: Ninety-three KTRs were matched with 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition, a recent case-control study with 306 participants ( n = 204 KTRs and 102 hemodialysis patients) showed that short-term BPV levels are significantly lower in KTRs than in age and sex-matched hemodialysis patients [28]. Finally, in a recent work from our group comparing short-term BPV between KTRs and predialysis CKD individuals (matched for age, sex and estimated glomerular filtration rate), we found no significant differences between the two groups in all BPV indices studied except for DBP-SD [29].…”
Section: Discussionmentioning
confidence: 84%
“…In addition, a recent case-control study with 306 participants ( n = 204 KTRs and 102 hemodialysis patients) showed that short-term BPV levels are significantly lower in KTRs than in age and sex-matched hemodialysis patients [28]. Finally, in a recent work from our group comparing short-term BPV between KTRs and predialysis CKD individuals (matched for age, sex and estimated glomerular filtration rate), we found no significant differences between the two groups in all BPV indices studied except for DBP-SD [29].…”
Section: Discussionmentioning
confidence: 84%
“…In a comparative study of KTR and CKD patients (matched for age, sex, and estimated glomerular filtration rate, n = 93 per group) BP levels, BP trajectories, and short-term BP variability indices were not different between KTR and CKD patients except for a slightly higher nighttime diastolic blood pressure (DBP) and slightly lower DBP standard deviation in KTR [20 ▪ ]. In addition, short-term BP variability did not change significantly at 3 and 12 months posttransplant compared to the baseline BP variability 1-month pretransplant [21 ▪ ].…”
Section: Blood Pressure Measurement Modalities In Kidney Transplant R...mentioning
confidence: 95%
“…The 2023 ESH Guidelines also discuss in considerable length the management of hypertension in kidney transplant recipients (KTRs) [ 1 ]. The guidelines discuss that kidney transplantation per se is associated with significant improvements in BP (8/5 mmHg in ambulatory BP) in the short- and mid-term post-transplant periods along with reduction in antihypertensive agents [ 103 , 104 ]; as such, ambulatory BP in KTRs is significantly lower than that in carefully matched hemodialysis patients and similar to patients with CKD with matched kidney function [ 105 , 106 ]. Despite these improvements, hypertension represents the most prevalent comorbidity post transplantation, with ABPM studies estimating hypertension prevalence in >95% of KTRs [ 107 ].…”
Section: Hypertension In Kidney Transplant Recipientsmentioning
confidence: 99%